Peran Keluarga Dalam Membentuk Kemampuan Berkomunikasi Anak Usia Dini Melalui Metode Bermain Peran: Perspektif Pendidikan Agama Kristen - Yudita Nismani Nduru; Jemy Saleky Combi; Suardin Zai; Lily Peggy Kawatu (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
In the context of Christian religious education, the role of the family in shaping early childhood communication through role-playing methods is essential. Through this approach, families play a key role in bringing Christian religious values into children's daily lives. Role playing is a means of encouraging active learning, where children are directly involved in the learning experience. Therefore, the aim of writing this article is to explain the role of the family in shaping early childhood communication through role-playing methods from a Christian religious perspective. The writing method uses a descriptive qualitative approach with the library research method. Data collection techniques through analysis of books, journal articles and websites that contain data related to research. The results show that this method helps in developing children's social and emotional skills, as well as helping to resolve conflicts and build healthy relationships within the family. By playing roles related to the teachings of the Christian religion, children learn to apply the principles of morality in their daily actions, and strengthen their overall character.